The Effectiveness of Teaching Programme Regarding Prevention and Management Napkin Dermatitis in Allahabad - Jemy Joseph; Shiju Mathew (Intelektual Pustaka Media Utama, 2013)
The neonates are unique in several ways in comparison with older children and adults which render them highly susceptible to severe dermatological disorders. Skin diseases in infancy and childhood often-present patterns, which may diverge from the same diseases in adults. Infants can get a variety of skin diseases, and some are more common than others. Infants are particularly at risk for developing diaper dermatitis and its potential consequences. It is one of the most common skin problems in infants and children, affecting between 7 and 35 per cent of infants at some point. Diaper rash occurs most commonly in infants between ages nine and 12 months, but can occur at any time the child wears a diaper. The present study was conducted to assess the effectiveness of structured teaching programme on prevention and management of napkin dermatitis in infants’ on mothers residing at Rural Naini, Allahabad. The conceptual framework set up for the study is Conceptual framework based on modified general system theory (Bertalamffy & JW Kenny). The model which has four phases i.e. input, throughput, output and feedback, context, It provide comprehension, systematic and continuous ongoing frame work for program evaluation and hence helped the investigator to assess the effectiveness of structured teaching programme on prevention and management of napkin dermatitis in infants and assess the level of knowledge gained by the mothers regarding prevention and management of napkin dermatitis in infants. In this study various literature was reviewed which includes, the research design selected for the study was pre experimental research design of one group pre-test post-test design. The independent variable was structured teaching programme and dependent variables were level of knowledge of mothers in pre-test and post-test.DOI: http://dx.doi.org/10.11591/ijphs.v2i1.1334